Aerodynamic measurements : from physical principles to turnkey instrumentation - Russo, Giuseppe P. (Cambridge, U.K. ; Philadelphia, Pa. : Woodhead Pub., 2011)
"Aerodynamic Measurements presents the most comprehensive review of the theoretical bases which experimental techniques used in aerodynamics are based on. Limitations of each method in terms of accuracy, response time, and complexity are addressed. The book will serve as a guide in choosing the most pertinent technique for each type of flow field including: 1D, 2D, 3D, steady or unsteady, subsonic, supersonic or hypersonic. It also describes the evolution of specific techniques from old-fashioned mechanical processes to modern computerized versions aiding students and practitioners to understand results of their findings."--
Pressure sensors -- Velocity and mass flow by pressure measurements -- Hot wire anemometer -- Laser anemometry -- Temperature measurements -- Flow visualization -- Measurements of aerodynamic forces.
Includes bibliographical references and index.
Keywords: Aerodynamic measurements; TECHNOLOGY & ENGINEERING -- Engineering (General); Aerodynamic measurements; Aerodynamik; Messung; Aerodynamic measurements; Air flow -- Measurement; Air flow